2011
DOI: 10.1016/j.joca.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis-like damage of cartilage in the temporomandibular joints in mice with autoimmune inflammatory arthritis

Abstract: Summary Objective To study temporomandibular joint (TMJ) involvement in an autoimmune murine model of rheumatoid arthritis (RA), a disease characterized by inflammatory destruction of the synovial joints. Although TMJ dysfunction is frequently found in RA, TMJ involvement in RA remains unclear, and TMJ pathology has not been studied in systemic autoimmune animal models of RA. Methods Proteoglycan (PG) aggrecan-induced arthritis (PGIA) was generated in genetically susceptible BALB/c mice. TMJs and joint tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
(55 reference statements)
3
14
0
3
Order By: Relevance
“…On the other hand, the proteoglycan (PG) aggrecan‐induced arthritis (PGIA) model described by Ghassemi‐Nejad et al is an autoimmune arthritis model . The authors compared the limb joints to the TMJ and observed that although destructive synovitis occurred in the limbs, there were no histological and immunohistochemical signs of inflammation in the TMJ, hence confirming our findings.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, the proteoglycan (PG) aggrecan‐induced arthritis (PGIA) model described by Ghassemi‐Nejad et al is an autoimmune arthritis model . The authors compared the limb joints to the TMJ and observed that although destructive synovitis occurred in the limbs, there were no histological and immunohistochemical signs of inflammation in the TMJ, hence confirming our findings.…”
Section: Discussionsupporting
confidence: 87%
“…The authors compared the limb joints to the TMJ and observed that although destructive synovitis occurred in the limbs, there were no histological and immunohistochemical signs of inflammation in the TMJ, hence confirming our findings. Only in severe cases of arthritis, structural damages were seen in the TMJ . However, although these results are similar to ours, the evaluation of the TMJ was performed at days 49 and 50, thus at a more advanced RA stage .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Research on TMJ OA involving animal models is still developing (2, 10–14). Currently, TMJ disorder diagnoses are based on non-specific symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…An OA animal model is an important tool in understanding TMJ disease (2, 10, 15, 18). Human studies can only describe TMJ OA, whereas animal models may elucidate a cause and effect relationship that might allow for TMJ disease reversal and a universal understanding of TMJ OA pathobiochemistry that is not currently available (14).…”
Section: Introductionmentioning
confidence: 99%